Pyridine‐Fused Bis(Norcorrole) through Hantzsch‐Type Cyclization: Enhancement of Antiaromaticity by an Aromatic Bridge. (31st July 2017) - Li, Xiaofang; Meng, Yankui; Yi, Pinggui; Stępień, Marcin; Chmielewski, Piotr J.
Abstract: A non‐catalytic condensation of Ni II β‐aminonorcorrole with aryl aldehydes is shown to produce a family of pyrromethane dimers that undergo deaminative cyclization to yield pyridine‐fused bis(norcorrole)s comprising two antiaromatic macrocycles communicating by an aromatic moiety. The new compounds were characterized by spectroscopic, structural, and electrochemical methods supported by DFT calculations, all of which revealed unexpected antiaromaticity enhancement in the fused system.